A Forest of Stories for a Girl in Search of Herself: The Snow Forest as a Narrative Scene in Sophie Andersonʼs The Girl Who Speaks Bear - Caterina Balistreri Bonsaver (Barnelitterært Forskningstidsskrift)
In the novel The Girl Who Speaks Bear by Sophie Anderson, twelve-year-old Yanka, adopted when she was two and struggling to fit in, heads for The Snow Forest in search of answers about her past. In her quest for her roots, she meets characters from famous folktales. These tell her stories that help the girl fill the gaps in her fragmented identity. In turn, Yanka herself becomes a storyteller. In this paper I will investigate the role of the forest in the novel, basing my discussion on previous analyses of the forest as a topos in folktales as well as on the concept of liminality and on Adriana Cavareroʼs study of the link between narrative and selfhood. I will argue that Andersonʼs fictional forest offers itself as a fluid, open environment that paradoxically affirms the possibility of identity as endowed with meaning, unity, and uniqueness by assigning a specific role to storytelling.